2017
DOI: 10.1292/jvms.16-0471
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zinc supplementation on Shiga toxin 2e-producing <i>Escherichia coli in vitro</i>

Abstract: Swine edema disease is caused by Shiga toxin (Stx) 2e–producing Escherichia coli (STEC). Addition of highly concentrated zinc formulations to feed has been used to treat and prevent the disease, but the mechanism of the beneficial effect is unknown. The purpose of the present study was to investigate the effects of highly concentrated zinc formulations on bacterial growth, hemolysin production, and an Stx2e release by STEC in vitro. STEC strain MVH269 isolated from a piglet with edema disease was cultured with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…Figure 6 showed that ZnO NPs -regulated the expression of the Stx2 gene, and there was a strong correlation between the down-regulation of the Stx2 gene and ZnO NPs concentrations. These results agree with previous studies that clarified that zinc exerts inhibitory effects on STEC strains and Stx expression (Crane et al, 2011;Crane et al, 2014;Uemura et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Figure 6 showed that ZnO NPs -regulated the expression of the Stx2 gene, and there was a strong correlation between the down-regulation of the Stx2 gene and ZnO NPs concentrations. These results agree with previous studies that clarified that zinc exerts inhibitory effects on STEC strains and Stx expression (Crane et al, 2011;Crane et al, 2014;Uemura et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, ZnO NPs suppressed Shiga toxin production. This result is supported by the finding of Uemura et al (2017), who reported a significant reduction in the cytotoxic activity of Stx2 in zinc-supplemented media compared to the control. Also, quantitative real-time PCR (qPCR) was performed to detect the Stx2 gene.…”
Section: Discussionsupporting
confidence: 77%
“…It is also known that, in growth conditions, Zn can specifically inhibit the expression of Shiga toxin by blocking the regulation of its production. In addition, Zn is more potent and efficient than other metals such as iron, manganese, and nickel in reducing the production of Shiga toxin (Crane et al, 2014;Uemura, Katsuge, Sasaki, & Goto, 2017). Taking into account that our experiments were done with EHEC supernatant (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as multidrug-resistant bacteria have been reported, antibiotics need to be selected appropriately [ 1 ]. As an alternative method, high amounts of zinc oxide may be added to feed [ 3 ], but there are concerns about the increase of drug-resistant bacteria and environmental pollution by zinc. Therefore, the exploitation of other control tools for ED, such as vaccines, is desired.…”
Section: Introductionmentioning
confidence: 99%